Factors Affecting Fishers’ Attitude and Willingness to use Cage Aquaculture as an Alternative Livelihood for Reducing Fishing Pressure in Haor Areas, Bangladesh - Mohammad Bodrul, Munir; Shahidul Islam, Bhuiya; Abdul, Hannan; Fozlul, Kabeer; Md. Jamal, Hossain; Alam, AKM Nowsad (UNIMAS Publisher, 2021)
Inland capture fisheries are providing cost of livings of about 1.2 million BDT in Bangladesh. However, overexploitation causing the declination of the abundance of native fish species which adversely affects the livelihoods of haor dwellers. The present study was conducted in two haor villages (Sutarpara and Changnoagaon) of Kishoreganj, Bangladesh to explore the factors (economic and non-economic) affecting fishers’ attitude and willingness about cage aquaculture considered as livelihood alternative for reducing fishing pressure. The methodologies applied to do this study were semi-structured face-to-face interview, key informants and questionnaire survey using Likert scale (LS), focus group discussions (FGD). The result revealed that willingness to switch from traditional way of fishing to cage aquaculture activities was significantly (P<0.05) higher in those fishers’ groups that had more inclination in fishing activities. Simultaneously, non-economic factors like powerful traders and fishers, traditional belief, taking risk, launching period of cage aquaculture venture and investment duration played vital role in decisions on whether to fish or not. The economic factors were fewer in number than non-economic factors. This comparative research is significantly important for future social aquaculture researchers as well as the country policy makers for giving emphasis to gather data based on the prevailing economic and non-economic factors to innovate alternative livelihood activity concurrently.